Basic MRI for the liver oncologists and surgeons - Vu LN; Morelli JN; Szklaruk J (Journal of Hepatocellular Carcinoma, 2018)
Lan N Vu,1 John N Morelli,2 Janio Szklaruk1 1Department of Radiology, The University of Texas MD Anderson Cancer Center, Houston, TX, USA; 2Department of Radiology, St. John’s Medical Center, Tulsa, OK, USA Abstract: Magnetic resonance imaging (MRI) is the modality of choice for liver imaging due to its superior contrast resolution in comparison with computer tomography and the ability to provide both morphologic and physiologic information. The physics of MR are complex, and a detailed understanding is not required to appreciate findings on an MRI exam. Here, we attempt to introduce the basic principles of MRI with respect to hepatic imaging focusing on various commonly encountered hepatic diseases. The purpose is to facilitate an appreciation of the various diagnostic capabilities of MR among hepatic oncologists and surgeons and to foster an understanding of when MR studies may be appropriate in the care of their patients. Keywords: basic MRI liver, HCC, tumor restricted diffusion, Eovist